The views and experiences of fathers regarding their young child's intellectual and developmental disability diagnosis: findings from a qualitative study - Brown, Michael; Marsh, Lynne; McCann, Edward (My University, 2020)
Aims and objectives: The aim of this paper is to report on fathers’ responses to their child’s diagnosis of intellectual and developmental disability (IDD), their expectations of fatherhood and their motivation for participating in research.Background: There is a growing interest in understanding the experiences of fathers of children with IDD given the transformation of the structural change of fathers’ roles within the family and wider society. Therefore, their voices need to have a more dominant research focus regarding learning of a child’s diagnosis, their expectations of fatherhood and their motivations for participating in research. Design: A secondary analysis of a qualitative study that initially explored the views and experiences of fathers of young children with intellectual and developmental disabilities (IDD) was used to address the new research questions.Methods: A total of 10fathers(n=10) consented to participate in semi-structured interviews. Secondary analysis of data were thematically analysed. Results: This paper specifically reports on three themes following a secondary analysis of the primary data (i) learning of a child’s diagnosis (ii) expectations of fatherhood and (iii) what motivates fathers to share their story. Conclusions:The study inform and develops further understanding the international evidence-base of learning of a child’s diagnosis, the expectations of fatherhood and what motivates fathers to share their story of being a father of a young children with IDD. Nurses have important contributions to make in meeting the needs of fathers and there are specific areas to consider in terms of practice, education and research that require further attention and development to ensure fathers distinct needs regarding their child’s diagnosis of IDD are known and responded to effectively. Relevance to clinical practice.This study highlights that from the time a diagnosis of a child’s disability is confirmed, fathers experience a competing range of mixed emotions. Healthcare professionals including nurses must be aware that even the words used at a disclosure can impact on how fathers process the news. Therefore, it is critical that healthcare professionals are aware and educated about their roles, responsibilities and best practice guidelines that could be used to underpin their practice at the time of disclosure to improve future care and support for fathers and the wider family.
PUBLISHED
Keywords: Fathers; Families; Children; Diagnosis; Education; Developmental disabilities; Intellectual disabilities; Intellectual disability; Inclusive Society; AUTISM; FAMILIES; FATHERS; Intellectual Disability; fathers role